Magnetic nanoparticles: Applications in gene delivery and gene therapy. (18th May 2016) - Majidi, Sima; Zeinali Sehrig, Fatemeh; Samiei, Mohammad; Milani, Morteza; Abbasi, Elham; Dadashzadeh, Kianoosh; Akbarzadeh, Abolfazl
Abstract : Gene therapy is defined as the direct transfer of genetic material to tissues or cells for the treatment of inherited disorders and acquired diseases. For gene delivery, magnetic nanoparticles (MNPs) are typically combined with a delivery platform to encapsulate the gene, and promote cell uptake. Delivery technologies that have been used with MNPs contain polymeric, viral, as well as non-viral platforms. In this review, we focus on targeted gene delivery using MNPs.